Prevalence of blood-borne infections in forensic samples: Epidemiology in areas of Chiba, Japan. (August 2022) - Okaba, Keisuke; Motomura, Ayumi; Horioka, Kie; Inokuchi, Go; Chiba, Fumiko; Hoshioka, Yumi; Saito, Naoki; Makino, Yohsuke; Torimitsu, Suguru; Yamaguchi, Rutsuko; Tsuneya, Shigeki; Yajima, Daisuke; et al.
Abstract: Objectives: To statistically clarify the prevalence and risk factors of infections in forensic autopsy cases in Chiba Prefecture, Japan. The aim was to improve preventive measures against infection in forensic autopsies. Methods: We retrospectively investigated the positive detection rates of five infections (hepatitis B, HBV; hepatitis C, HCV; human immunodeficiency virus, HIV; human T-lymphotropic virus, HTLV; Treponema pallidum, TP) using 1491 samples obtained in forensic autopsy at our facility from 2014 to 2018. In addition, risk factors related to infection such as methamphetamine and tattoos were analyzed. Pearson's chi-square test was used for statistical analysis, and the difference was judged to be significant at p < 0.05. Results: Among our samples, 9.0% of cadavers tested positive for infection, and the prevalence rates for HBV, HCV, HIV, HTLV, and TP were 1.0%, 6.7%, 0.3%, 0.7%, and 1.1% respectively. Statistically, cadavers linked to information about methamphetamine use had a 7.2 times higher rate of infection, and those with tattoos had a 5.6 times higher rate of infection, with HCV being the predominant cause. Conclusions: To limit the risk of infection among autopsy workers, cadavers and samples should be handled on the presupposition that the bodies are at risk of infections. It is also important to obtain as much information as possible about the medical history and potential illegal drug use to help assess the risk of infection in a patient during forensic autopsy. We propose that all autopsy cases should be screened for infections whenever possible. Highlights: Prevalence and risk factors for infection in forensic autopsy in Japan were examined. Prevalence rates of HBV, HCV, HIV, and HTLV were 1.0%, 6.7%, 0.3%, and 0.7%. The prevalence of syphilis, which is previously unreported, was 1.1%. Cadavers with information of methamphetamine use had 7.2× higher risk of infection. Cadavers with tattoos had 5.6× higher risk of infection.